Network and Systems Biology Approaches in Glial Cells - Vera González, Julio; Cantone, Martina; Blume, Christina (Systems Medicine: Integrative, Qualitative and Computational Approaches. Volume 2: Application Areas, 2021)
The central nervous system (CNS) is composed of many populations of functionally specialized, spatially organized and highly interacting cells, including neurons, astrocytes, oligodendrocytes and microglia. The ability of these cell populations to sustain their physiological functions is regulated by complex molecular networks. Experimental techniques that are able to produce high-throughput data (HTD) accounting for changes at the transcriptomic, proteomic or epigenomic level are revolutionizing neurobiology and helping in understanding the regulation of these molecular networks. However, HTD have to be interpreted in the context of the spatiotemporal interactions among molecular factors and cell types making up the CNS, and therefore one is forced to analyze the data from a systemic perspective. In Systems Biology mathematical modeling and Bioinformatics tools are combined to analyze and integrate HTD data. These data are used to elucidate the structure and regulation of molecular networks controlling cellular function(s) and phenotype(s) during development, normal functioning and pathophysiological conditions. In this article, we introduce the basics of Systems Biology and discuss case studies in which this methodology has been utilized to understand the regulation of glial cells in development and pathogenesis.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Astrocytes; Bioinformatics; Computational modeling; Mathematical modeling; Microglia; Morphogenes; Network biology; Oligodendrocytes; RNA-Seq; Sox factors; Systems biology; Transcriptional profiling